PENGAWETAN LIMA JENIS KAYU SECARA PELABURAN MEMAKAI DUA JENIS BAHAN PENGAWET - Sasa Abdurrohim (Jurnal Penelitian Hasil Hutan, 1996)
Five air dried timber species measured 2.5 x 5 x 10 cm was brushed by preservative in one of the broader side for four,  seven and ten times which similar with 1.25 g, 1.75  g and 2.25 g preservative.   The preservative  used  were Xylamon 5. 61  OC and  Cuprinol  118 L,  with the replication per  treatment were ten.  Two weeks after treatment preservative penetration  in all samples was measured.The  results  showed   that  the  preservative  penetration  of  all  treatment  did  not  mee trequirements for  timber housing. Additional brushing may be could improve penetration  and meet the standard but it will be costly. The cost offour,  seven and ten times brushing if appliedin door frame  are Rp  245,530,-  Rp.  343,742,-  and Rp.  44J,953,-  per  m3  with the price  of preservative Rp. 13,500,- per liter.Key words:  brushing,  Xylamon, Cuprinol, penetration